2021
DOI: 10.3390/su13095239
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Climate Change and Land-Use Impacts on Drinking Water Resources in Karstic Catchments (Southern Croatia)

Abstract: The Mediterranean freshwater resources, mostly represented by groundwater, are under increasing pressure due to natural and anthropogenic factors. In this study, we investigated possible negative effects of climate change and land-use practices on water quality and availability from five springs in the karstic catchments in southern Croatia. The investigated springs are used in the regional public water supply system. Firstly, we employed hydrogeochemical field and laboratory analyses to detect possible traces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The increasing intensity of droughts, driven by longer dry periods and shorter wet periods have made this region one of the most susceptible to soil degradation and desertification in Europe (Ferreira et al, 2020). Carbonate formations and karst features characteristic of this area are subjected to the global problem of climate change, as many karst springs, rivers, and streams face significant hydrological changes such as increased flow intermittence characterised by seasonal loss of flow and surface drying (Frollini et al, 2022;Patekar et al, 2021;Sivelle et al, 2021;Stubbington et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing intensity of droughts, driven by longer dry periods and shorter wet periods have made this region one of the most susceptible to soil degradation and desertification in Europe (Ferreira et al, 2020). Carbonate formations and karst features characteristic of this area are subjected to the global problem of climate change, as many karst springs, rivers, and streams face significant hydrological changes such as increased flow intermittence characterised by seasonal loss of flow and surface drying (Frollini et al, 2022;Patekar et al, 2021;Sivelle et al, 2021;Stubbington et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Croatia hosts many karst features, as almost half of the country is karst territory (Patekar et al, 2021). Most recognized karst features are the tufa barriers, which are formed by interactions between precipitation of carbonate minerals and resident organisms at specific ambient conditions (Golubić et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the research results are mostly landuse model simulations and predictions [10][11][12] and driving mechanisms [13,14]. Recent studies showed that the value of ecosystem services [15], water-resource utilization [16], regional ecosystem environment patterns [17], and other activities are directly or indirectly affected by land-use changes. Zhang [18] selected socioeconomic data to build a complex driving mechanism model, discovering that the total regional population, GDP, and other Sustainability 2021, 13, 10263 2 of 19 socioeconomic factors are the main driving forces of land-use system changes.…”
Section: Introductionmentioning
confidence: 99%
“…Karst groundwater provides drinking water for 10% of the world's population, and is an indispensable resource for ecosystems, agriculture and groundwaterdependent activities [1,2]. However, the sustainable utilization of karst groundwater is facing challenges in terms of both quantity and quality, since karst aquifers are extremely vulnerable to climate and anthropic pressures [3][4][5][6]. Karst groundwater resources are particularly vulnerable to contamination resulting from intense agriculture and other anthropogenic activities, and the quality of karst groundwater continues to deteriorate, resulting in water quality-based water shortages in karst regions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%